Flow pattern at a river diffluence at the alluvial system of the Paraná River - Morell, Mariana Inés (2014)
This communication presents field and numerical data depicting the flow pattern formed at a diffluence of the Colastiné River, Argentina, where one branch accesses the local harbour. The harbour has been in decline since the 1970s due to costly maintenance dredging of the access channel. The objective of this work is thus twofold: to show the persistence of the flow pattern developed at the diffluence despite recent morphological changes seen at the site, and to test a possible solution to the access channel sedimentation problem. Knowledge gained during the execution of the study helped to validate a code developed to process field data captured with two acoustic Doppler current profilers (ADCPs). The results confirm that both branches are prone to developing secondary currents. Simulations show that an engineering intervention downstream of the bifurcation can establish a self-dredging flow reversal along the access channel, turning the actual diffluence into a stable confluence.